Photoinduced charge transfer by one and two-photon absorptions: physical mechanisms and applications. Issue 30 (23rd July 2018) - Zong, Huan; Wang, Xinxin; Quan, Jun; Tian, Chunhua; Sun, Mengtao
Abstract : We review photoinduced charge transfer in organic solar cells without and with an external electric field and then we introduce the visualization methods of the transition density, charge difference density and transition density matrix for the analysis of the photoinduced charge transfer in a neutral system and a charged system excited by one-photon and two-photon absorption. Abstract : We review photoinduced charge transfer in organic solar cells without and with an external electric field and then we introduce the visualization methods of the transition density, charge difference density and transition density matrix for the analysis of the photoinduced charge transfer in a neutral system and a charged system excited by one-photon and two-photon absorption. This review will not only promote a deeper understanding of the available theories and methods of PICT, but also lead to further developments in this field.